DEWAN PERWAKILAN RAKYAT SEBELUM DAN SESUDAH AMENDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Merina Nurmiati; Dodi Haryono; Emilda Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The People's Representative Council is an organ that exercises direct legislative powers in the 1945 constitution. The phenomena that occurred during the New Order era tended to benefit the executive branch. The House of Representatives of the people of the new order is only used as a